Efektivitas Bahan Ajar Digital Interaktif pada Kemampuan Membaca dan Memirsa Murid Sekolah Dasar - Puspa Sari Kurniawati; Akbar Al Masjid; Banun Havifah Cahyo Khosiyono (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study aims to examine the effectiveness of interactive digital teaching materials on students’ ability to read and view fairy tales. The research subjects were 26 sixth-grade students of SD Negeri Sumberadi 1 Mlati, Sleman. This study employed a pre-experimental method using a one-group pretest–posttest design. Data were collected through observation and tests. The data analysis techniques used were the N-gain score and the paired sample t-test.The results showed that the mean pretest score was 51.9, while the mean posttest score was 88.5, indicating an average increase of 29.9 points. The N-gain score was 0.608, indicating a moderate improvement. The Q–Q plot analysis showed that the residuals were normally distributed, as the data points followed the diagonal line, indicating a balanced distribution without significant deviation. Therefore, the interactive digital teaching materials are considered feasible for use, as they not only improve students’ scores but also make learning outcomes more consistent. The paired sample t-test result showed a significance value of 0.000, which is lower than the significance level of 0.05, proving that interactive digital teaching materials are significantly effective in improving elementary school students’ reading and viewing abilities.